Partisipasi Masyarakat dalam Pengelolaan Sampah di Tempat Pengolahan Sampah Terpadu Reduce, Reuse, Recycle Desa Penarungan, Kecamatan Mengwi, Kabupaten Badung - Saputra, Putu Sandi; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT This research aims to describe community participation on waste management in TPST 3R of Penarungan Village. The method used in this research is qualitative method with descriptive type with data collection techniques in the form of observation, interviews, and documentation. The theory used is community participation according to Cohen and Uphoff with indicators of community participation in decision making; Implementation of Acceptance and utilization of results; Evaluation. The result of this research shows community participation in decision making is still lacking. One form of participation that still lacking is the willingness of people to buy compost and limitation the creativity of the group to recycle anorganic waste.the benefits of waste management have not been felt because it has no income. Community participation in an evaluation form group's internal; and evaluation by the people who become customers in the form of comments and suggentions on the implementation of TPST 3R. Keywords:Community Participation, Waste management Reduce, Reuse, Recycle, Village of Penarungan.